Automated Detection of Machine-Generated Tweets Using Hybrid Deep CNN and FastText Embeddings - Ch. Sreelatha, K. Pavani, L. Reshmi Bhavishya, K. Sri Thanay, V. Abhiram (Journal of Computational Analysis and Applications (JoCAAA), 2025)
Deepfake technology has emerged as a serious challenge to the authenticity of information shared onsocial media, particularly in domains such as politics and entertainment where fabricated videos and AIgenerated content frequently fuel misinformation. The goal of this research is to design a robust deep learning–based framework capable of detecting deceptive